Actualization of Thinking KH. Ahmad Shiddiq About Education Leadership of National Insight - Halid, Ahmad (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
This article examines the thoughts of KH. Ahmad Siddiq on the educational leadership model with a national perspective. There is a very interesting lesson from his thoughts so he deserves to be called a national hero because he is a cleric who has national insight who can unite the Indonesian people and accept Pancasila as the basis of the Indonesian state. This study uses a descriptive qualitative model with library data collection and data validity using data triangulation. KH. Ahmad Siddiq has a proportional thought, ideology and religion are not two things that must be chosen one while discarding the other. In the relationship between religion and Pancasila, the two can support each other and strengthen each other, the two are not contradictory and should not be contradicted.